A survey of element toxicities in wheat grown in naturally waterlogged farmer's sodic fields of eastern Uttar Pradesh, India. (16th March 2017) - Singh, Surendra Pratap; Setter, Tim L.
ABSTRACT: This survey examined the element toxicities in wheat grown in naturally waterlogged farmer's sodic fields. Seven sites located in three districts (Faizabad, Pratapgarh, and Ambedkar Nagar) of eastern Uttar Pradesh, India were selected for the study. The data on soil redox potential (Eh), soil pH, soil electrical conductivity (EC), waterlogging duration, and crop age during waterlogging were recorded at the time of plant sampling in all the sites. Waterlogging caused a reduction of 21% to 65% in shoot dry weight in the survey sites. During waterlogging, the concentrations of iron (Fe), aluminum (Al), and sodium (Na) in leaves increased dramatically; the values of these elements were many folds higher than their reported critical toxicity levels (Fe-100 ppm, Al-50 ppm, and Na-8000 ppm, respectively). The results support the hypothesis that element toxicities occur during waterlogging in wheat grown in farmer's sodic field and identified Fe, Al, and Na toxicities as a major constraint for wheat production in the study area.